AGRO-MORPHOLOGICAL VARIATION AND GENETIC DIVERSITY ASSESSMENT OF TUNISIAN SUNFLOWER (HELIANTHUS ANNUUS L.) ACCESSIONS USING MICROSATELLITE MARKERS - T. Hosni; H. Chennaoui Kourda; S. Medimagh; N. Omri Ben Youssef; Z. Abbes; H. Ben Salah; M; Kharrat (Journal of Animal and Plant Sciences, 2023)
Sunflower (Helianthus annuus L.) is considered as one of the most important oilseed crops in the world. ‎In Tunisia, sunflower is cultivated in the Northern region of the country using local populations which are genetically not well studied. This study was conducted to evaluate the genetic variation of 33 accessions (26 local and 7 introduced) using 23 agro-morphological traits and 15 simple sequence repeats (SSR) markers. The variance analysis of the agro-morphological traits showed a significant variation among sunflower accessions. The relationship among the sunflower accessions was also performed by using the principal component analysis; the two first axes explained 54.4% of the total variability and showed that the accessions spread into five groups. The groups (G3 and G4) could be used to improve sunflower varieties with high performance especially for the diameter of the head and the weight of 1000 seeds characters. Ten among the 15 SSR primers used revealed clear polymorphic bands and were able to amplify 29 alleles with an average of 2.9 alleles per locus. The percentage of total polymorphism, the polymorphism information content (PIC) and the dissimilarity coefficient values varied from 50 to 100% with an average of 91%, from 0.35 to 0.75 with an average of 0.50, and from 0.00 to 0.81 with an average of 0.41, respectively. Cluster analysis of the SSR markers grouped accessions into 3 distinct groups. A significant correlation was observed among SSR markers and morphological traits. These results found in this study may be helpful for improvement of sunflower breeding programs.
Keywords: Helianthus annuus; genetic diversity; microsatellite; morphological characterisation; cluster analysis